Answer:
3
Step-by-step explanation:
Every group of candies eaten is 4 candies because Valerie eats 3 and her friend eats 1. 1+3 = 4 . 12/4 = 3
Answer:
-4
Step-by-step explanation:
to do this you use y2-y1/x2-x1
so this would be -4-8/1- - 2
-12/3 = -4
Answer:
x
=
ln
(
3
)
7
ln
(
3
)
+
ln
(
7
)
Step-by-step explanation:
Answer:
Step-by-step explanation:
-3x^4 -9x^3+ 15x^2
-3x^2 ( x^2 + 3x -5)
if you use quadratic formula (see image)
~~~~~~~~~~~~~~~~~~~~~~
10x^3 -35x^2 +6x -21
5x2(2x-7) +3(2x-7)
(5 + 3) (2x-7)